2010
DOI: 10.1590/s0037-86822010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of positivity for Trypanosoma cruzi in triatomine from municipalities in Southeastern Brazil, from 2002 to 2004

Abstract: INTRODUCTION: from an epidemiological point of view, more than 120 species of triatomine (Hemiptera, Reduviidae) are known. The occurrence and positivity for Trypanosoma cruzi in triatomines in 16 municipalities of the Triângulo Mineiro and Alto Paranaíba were evaluated from January 2002 to December 2004. METHODS: the triatomines were captured basically according to the classic norms of the National Health Foundation. The parasitological exams of the triatomines were conducted according to the technique descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
3
9
1
1
Order By: Relevance
“…The frequency of capture of T. sordida was higher than that of the other triatomines, which confi rms the results of previous entomological surveys in which this species was frequently found 3,14,25,26 . Although previous studies have reported a low rate of T. cruzi infection 2,3,25 , the present study suggests that these values may be underestimated and that PCR is essential as a tool for detection in offi cial surveys.…”
Section: Conflict Of Interestsupporting
confidence: 87%
“…The frequency of capture of T. sordida was higher than that of the other triatomines, which confi rms the results of previous entomological surveys in which this species was frequently found 3,14,25,26 . Although previous studies have reported a low rate of T. cruzi infection 2,3,25 , the present study suggests that these values may be underestimated and that PCR is essential as a tool for detection in offi cial surveys.…”
Section: Conflict Of Interestsupporting
confidence: 87%
“…The strong association of P. megistus with chickens coincides with the data reported by Villela et al 5 and Paula et al 15 for the State of Minas Gerais. Due to the availability of food sources, wild triatomines are attracted to the peridomicile environment, which is a very important environment for maintaining the infestation of the household and can be the source of infestation for the house interior 5 .…”
supporting
confidence: 91%
“…The ability of T. sordida to colonize both natural and artificial ecotopes, along with its high tolerance to environmental change 15 , makes it an important vector in the parasite cycle and difficult to control. Despite T. sordida being considered a species that prefers to infect birds, the high rates of peridomestic infestation (20%) and parasitic infection (18%) suggest that surveillance is necessary because the mere coexistence with a vector increases the possibility of human infection 16 besides presenting a higher rate of infection when compared with other surveys 8,17,18 . Other studies showed that T. sordida is the most frequent in captures 17 -also peridomestic and domiciliary infestation reaching 86.6% 8 and 47.7%…”
Section: Discussionmentioning
confidence: 99%